Timing of Gestational Weight Gain on Fetal Growth and Infant Size at Birth in Vietnam - Young, Melissa F.; Nguyen, Phuong Hong; Addo, O. Yaw; Pham, Hoa; Nguyen, Son; Martorell, Reynaldo; Ramakrishnan, Usha (Public Library of Science, 2017)
To examine the importance of timing of gestational weight gain during three time periods: 1: ≤ 20 weeks gestation), 2: 21-29 weeks) and 3: ≥ 30 weeks) on fetal growth and infant birth size.Study uses secondary data from the PRECONCEPT randomized controlled trial in Thai Nguyen province, Vietnam (n = 1436). Prospective data were collected on women starting pre-pregnancy through delivery. Maternal conditional weight gain (CWG) was defined as window-specific weight gains, uncorrelated with pre-pregnancy body mass index and all prior body weights. Fetal biometry, was assessed by ultrasound measurements of head and abdomen circumferences, biparietal diameter, and femoral length throughout pregnancy. Birth size outcomes included weight and length, and head, abdomen and mid upper arm circumferences as well as small for gestational age (SGA). Adjusted generalized linear and logistic models were used to examine associations.Overall, three-quarters of women gained below the Institute of Medicine guidelines, and these women were 2.5 times more likely to give birth to a SGA infant. Maternal CWG in the first window (≤ 20 weeks), followed by 21-29 weeks, had the greatest association on all parameters of fetal growth (except abdomen circumference) and infant size at birth. For birth weight, a 1 SD increase CWG in the first 20 weeks had 3 times the influence compared to later CWG (≥ 30 weeks) (111 g vs. 39 g) and was associated with a 43% reduction in SGA risk (OR (95% CI): 0.57 (0.46-0.70).There is a need to target women before or early in pregnancy to ensure adequate nutrition to maximize impact on fetal growth and birth size.ClinicalTrials.gov, NCT01665378.